Predictors of High-School Dropout Among Ultraorthodox Jewish Youth - Itzhaki-Braun, Yael; Itzhaky, Haya; Yablon, Yaacov B. (Frontiers in Psychology, 2020)
Focusing on the unique social characteristics of closed communities, the current study examined the predictors of high school dropout among Ultraorthodox Jewish youth, focusing on background variables (i.e., individual’s age, family’s religious group affiliation, and other high school dropout(s) in family); social resources (i.e., self-esteem and mastery); and parental conditional regard (PCR) and societal conditional regard (SCR), divided into positive and negative regard. Conducted in Israel among Ultraorthodox Jewish males, the study included 261 participants, ages 14-21 (M = 17, SD=1.17), who were at different stages in the dropout process. Path analysis modeling indicated that being a member of a newly religious family, or of a family in which another member had already dropped out of school, were predictors of dropout. Surprisingly, personal resources were not found to be a predictor of dropout, whereas parental conditional regard and societal conditional negative regard (SCNR) were found to be the most significant predictors. Findings highlight the unique predictors of high school dropout among youth from the Ultraorthodox Jewish community, and the role of PCR and SCR in this process.